EFFICACY OF SPECIAL COATINGS IN THE TREATMENT OF TROPHIC ULCERS - Atakov, S.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. Trophic ulcers are the cause of household and cosmetic inconveniences, often patients experience pain, fear of physical exertion, and fear of damaging the lower limb since minimal trauma can lead to a rapid progression of the pathological process. Material and methods. A total of 186 patients with trophic leg ulcers of venous etiology, who were hospitalized in the multidisciplinary clinic of the Tashkent Medical Academy for the period from 2014 to 2022, were examined. All patients were randomized into a study group and a control group. Results. Based on the studies carried out, it has been shown that the method of using moisturizing wound coverings in patients with trophic ulcers of the lower extremities helps to improve the indicators of local microcirculation, stimulates the processes of purulent necrotic cleansing of ulcers from purulent-necrotic masses and bacterial flora, accelerates the appearance of granulation tissue and reduces the time of epithelialization of ulcer defects. Conclusion. The method of using moisturizing wound dressings against the background of complex pathogenetic therapy in patients with venous trophic ulcers of the lower extremities leads to a significant reduction in the treatment period.